Sites of the dictators : memories of authoritarian Europe, 1945-2020 - Núñez Seixas, Xosé M., 1966- 1966- (Routledge, Taylor & Francis Group, 2021)
"This book explores the changing evolution of memory debates on places intimately linked to the lives and death of different fascist, para-fascist and communist dictators in a truly transnational and comparative way. Using the concept of 'sites of the dictators', the author explains why is it so difficult to deal with some sites of memory linked to dead autocrats and discusses the potential of the 'Europeanization' of these 'dark' memories of the past. Exploring the imperatives of memory politics and how these are reconciled with local actors interested in exploiting the dictator's remembrance, it will be useful reading for students and scholars of history, politics and memory studies"--